Multiple paternity in a wild population of the corn mouse: its potential adaptive significance for females - Sommaro, Lucía Valeria (2015)
Mating with multiple males within a single reproductive event is a common female mating strategy in mice and voles, but its adaptive function is often unclear. In this study, we used 7 microsatellite loci to investigate if multiple paternity occurs in wild populations of the socially promiscuous Calomys musculinus. We also analyzed if multiple paternity increases litter size and/or genetic variability among offspring. In addition, we examined if multiple paternity occurs more frequently in litters conceived at high population density than those conceived at low population density. By genotyping 23 females and their 135 embryos (5.9 ± 1.6 SE pups per female), we found that 56.5% of the litters were sired by 2 or 3 males. We found no association between multiple paternity, litter size, and genetic variability. In addition, multiple paternity did not vary in relation to population density. Our results provide clear evidence of multiple paternity and offer the first genetic documentation of mating systems in mice in Argentina. We discuss the extent of multiple paternity in relation to potential adaptive strategies in female corn mouse.